Preeclampsia in Multiples: A Comparative Case Study on Dichorionic-Diamniotic Twin Pregnancy - Reny Faristin Putri Arifin; Via Rustiani; Wildan Firmansyah (Jurnal Indonesia Sosial Teknologi, 2024)
Multiple pregnancies have a 2-3 times greater risk of developing preeclampsia and have a significant long-term effect on both mothers and babies. The underlying cause of preeclampsia in women with multiple pregnancies is higher demand on the cardiovascular system, increased exposure of the chorionic villi, increased antiangiogenic substances compared to angiogenic substances and placental hypoperfusion. The condition of preeclampsia can worsen quickly, and without warning signs, it must be detected and managed appropriately; if the treatment is late, this condition can lead to eclampsia. The patient was referred with severe preeclampsia and multiple pregnancies with complaints of irregular contraction (+), a history of dizziness (-), nausea (-), vomiting (-), blurred vision (-), and breathlessness (-). Physical examination showed Blood pressure 188/125 mmHg with laboratory findings of proteinuria +3. Cesarean section and IUD insertion were performed. During and after surgery, there were no complications.